Sward structure and short-term herbage intake in Arachis pintoi cv. Belmonte subjected to varying intensities of grazing - Silva, G. P.; Fialho, C. A. [UNESP]; Carvalho, L. R.; Fonseca, L.; Carvalho, P. C.F.; Bremm, C.; Da Silva, S. C. (Cambridge University Press (CUP), 2018)
The use of forage legumes has been proposed as a means of generating sustainable grazing environments. Their limited use, particularly in tropical pastures, is partially due to the limited knowledge regarding the efficiency of utilization by animals. The present study characterized the sward structure, nutritive value and ingestive behaviour of dairy heifers in pastures of peanut cv. Belmonte under continuous stocking management. Treatments corresponded to sward heights of 5, 10, 15 and 20 cm, according to a randomized complete block design, with four replications. The following response variables were evaluated: vertical distribution of the morphological components within the sward, forage mass, nutritive value (simulated grazing), bite rate (BR), bite mass (BM) and short-term herbage intake rate (STIR). The top half of the sward height was mainly composed of leaves and the bottom half mainly of stolon and dead material regardless of management height. Greater values of neutral detergent fibre and acid detergent fibre were recorded during autumn, while higher values of in-vitro dry matter (DM) digestibility (0·85) occurred during spring regardless of management height for the grazed stratum. In relation to treatments, greater values of crude protein were recorded on swards managed at 5 cm (0·27) and 10 cm (0·26). Bite rate, BM and STIR varied with sward height, but not with a season of the year. The STIR followed a broken line response to sward height, with increasing values up to 13·1 cm (106 g DM/kg body weight). Sward structure played an important role in determining the STIR. To maximize the STIR of dairy heifers under continuous stocking management, swards should be managed at heights of not <13·1 cm.
Keywords: Continuous stocking management; forage peanut; intake rate; legumes; sward structure